Sermons on the book of Micah - Calvin, Jean, 1509-1564; Farley, Benjamin Wirt, 1935- (Phillipsburg, NJ Presbyterian and Reformed, 2003)
Includes indexes.
Translation of "Sermons sur le livre de Michee", edited by Jean-Daniel Benoit, Supplementa Calviniana, v. 5 (Neukirchen-Vluyn: Neukirchener Verlag des Erziehungsvereins, 1964.
Keywords: Bible. O.T. Micah -- sermons